3‐D Numerical Simulation and Analysis of the Flow Pattern in the Shot Sleeve of the Cold Chamber HPDC Process. Issue 1 (17th December 2018) - Laouar, Roudouane
Abstract: This work presents a 3d‐numerical study of the flow of molten metal in the shot sleeve of a horizontal high‐pressure die casting machine. The analysis of the flow pattern caused by the filling and the plunger motion can be of help in reducing porosity in manufactured parts caused by air entrapment. A particular attention has been paid to the flow and temperature field below the filling hole. The used numerical model is based on the conservation equations of mass, momentum and energy, and describes the free surface using the volume‐of‐fluid method.